2013
DOI: 10.1371/journal.pone.0062092
|View full text |Cite|
|
Sign up to set email alerts
|

S100A8 and S100A9 Are Associated with Colorectal Carcinoma Progression and Contribute to Colorectal Carcinoma Cell Survival and Migration via Wnt/β-Catenin Pathway

Abstract: Background and ObjectiveS100A8 and S100A9, two members of the S100 protein family, have been reported in association with the tumor cell differentiation and tumor progression. Previous study has showed that their expression in stromal cells of colorectal carcinoma (CRC) is associated with tumor size. Here, we investigated the clinical significances of S100A8 and S100A9 in tumor cells of CRC and their underlying molecular mechanisms.MethodsExpression of S100A8 and S100A9 in colorectal carcinoma and matching dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
63
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 68 publications
15
63
0
1
Order By: Relevance
“…A further study reported that S100A8 and S100A9 contribute to colorectal carcinoma cell survival and migration via the Wnt/β-catenin pathway. S100A8 and S100A9 increase total β-catenin levels and promote transcription of its target genes (c-myc and MMP7), resulting in the upregulation of the Wnt/β-catenin pathway (24). The present study confirmed that S100A8 and S100A9 is vital for the migration of CNE1 NPC cells, and indicated that MMP7 may be involved.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A further study reported that S100A8 and S100A9 contribute to colorectal carcinoma cell survival and migration via the Wnt/β-catenin pathway. S100A8 and S100A9 increase total β-catenin levels and promote transcription of its target genes (c-myc and MMP7), resulting in the upregulation of the Wnt/β-catenin pathway (24). The present study confirmed that S100A8 and S100A9 is vital for the migration of CNE1 NPC cells, and indicated that MMP7 may be involved.…”
Section: Discussionsupporting
confidence: 79%
“…At 48 h and 72 h, after the effects of the siRNAs had diminished, cell migration in the S100A8 and S100A9 siRNA-transfected experimental groups were restored to a certain degree, while scratched areas in the blank control, negative control and mock-treatment groups had filled with cells. At each time-point after scratching (24,48 and 72 h), the migration ratio of the S100A8 and S100A9 siRNA-transfected experimental groups was significantly lower compared with that of the blank control, negative control and mock-treatment groups (Tables III and IV). No significant differences were observed among the blank control, negative control and mock-treatment groups (P>0.05; Fig.…”
mentioning
confidence: 94%
“…Increasing evidence indicates that the expression of S100A8 is increased in CRC tissues and the elevated expression of S100A8 is associated not only with histological differentiation, but also with Dukes' stage and lymph node metastasis in CRC (9). In the present study, we found that S100A8 promoted the expression of miR-155 and the secretion of IL-1β and TNF-α through activation of the NF-κB signaling pathway in macrophages, eventually facilitating the migration of CRC cells, which occurred in the inflammation environment mimicked by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that S100A8 plays an important role in regulating tissue inflammation as a ligand of toll-like receptor 4 (TLR4) and/or receptor for advanced glycation end products (RAGE) (7,8). Aberrant expression of S100A8 has been found in different types of tumors including CRC (9) and the accumulation of S100A8 positive cells is always located in the invasive margin of colorectal carcinoma (10) which plays a critical role in the tumor microenvironment. Interestingly, mounting evidence indicates that the apical surface of the intestinal epithelium is exposed to lipopolysaccharides (LPS) from the lumen due to intestinal mucosal permeability and bacterial translocation (11).…”
Section: Introductionmentioning
confidence: 99%
“…As an inflammatory protein, it may serve a role in tumor-stromal interactions (14), and elevated levels of protein S100-A8 have been observed in numerous types of malignancy, including cutaneous squamous cell carcinoma (12), gastric adenocarcinoma (15) and kidney cancer (16). In addition, a previous study demonstrated a correlation between the expression levels of protein S100-A8 and colorectal carcinoma progression, during which this protein may contribute to colorectal carcinoma cell survival and migration via the Wnt/β catenin signaling pathway (17). To the best of our knowledge, the present study is the first to report differences in the expression levels of protein S100-A8 between fresh PBT and fresh PMLN tissues, screened using the iTRAQ proteomic technique.…”
Section: Introductionmentioning
confidence: 49%